LETRAS - Communication with Lines, Triangles and Rectangles - Ramos, Guilherme Matheus A.; Sales, Victor O. N.; Teixeira, César A. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
People may lose motor skills for different reasons, due to accidents or illnesses. Very serious diseases, such as Amyotrophic Lateral Sclerosis (ALS), evolve to the point of imposing severe motor restrictions, reaching situations where the patient is unable even to speak or perform movements, besides moving the eyes. An additional consequence for the sick person, besides needing support for all her necessities that require any movement, is the difficulty in communicating. It becomes essential, in such cases, the use of alternative communication facilities. Motivated for helping a sick person at advanced stage of ALS, unable to control even the act of blinking, we proceeded with studies and implementation of another device (camera + software) for eye tracking. The novelties of the proposed solution, compared to others that are based on the same principle, are: the independence of high precision eye-tracking devices, usually very expensive; it does not require patient accuracy to select symbols on virtual keyboards, or memorization of specific eye movements to express themselves. We present in this paper the rationale that guided the design decisions, some details of the development and some achieved results which suggest the proposal feasibility.